Tannery Wastewater Treatment Using Low Cost Coagulants with Simple Coagulation-Filtration Process - Barman, Bishnu Chandra; Juel, Md. Ariful Islam; Hashem, Md. Abul (Engineering International, 2017)
Tannery is the oldest industries in the world. It is characterized as pollutants generating industries, which produce wide varieties of high strength toxic residues. This study has been focused on the removal of physicochemical parameters of tannery wastewater through simple coagulation-filtration techniques using low cost coagulants. Standard methods were used for sampling and analysis. Removal efficiency was measured in terms of reduction of COD, BOD5, suspended solids (SS), total dissolved solids (TDS), conductivity and color. Several doses of coagulants e.g. alum, ferric chloride and their combination were used in treatment process. Maximum removal efficiency was obtained with the combination of alum and ferric chloride dosing at 75 mg/L in terms of color, BOD5, COD, TDS, SS and conductivity corresponding to 75%, 78%, 76%, 37%, 94% and 41% respectively and that were increased to92%, 82%, 80%, 48%, 98% and 51% respectively after sand-stone filtration. Ferric chloride and combination of alum and ferric chloride are recommended for the effective primary treatment of tannery wastewater. The filtration with multi-layer sand-stone filter was effective in removing of color, TDS, conductivity and SS.